Active transforming growth factor-β2 in the aqueous humor of posterior polymorphous corneal dystrophy patients - Stadnikova, Andrea; Dudakova, Lubica; Skalicka, Pavlina; Valenta, Zdenek; Filipec, Martin; Jirsova, Katerina (PloS one, 2017)
PURPOSE: Posterior polymorphous corneal dystrophy (PPCD) is characterized by abnormal proliferation of corneal endothelial cells. It was shown that TGF-β2 present in aqueous humor (AH) could help maintaining the corneal endothelium in a G1-phase-arrest state. We wanted to determine whether the levels of this protein are changed in AH of PPCD patients. METHODS: We determined the concentrations of active TGF-β2 in the AH of 29 PPCD patients (42 samples) and 40 cadaver controls (44 samples) by ELISA. For data analysis the PPCD patients were divided based on either the molecular genetic cause of their disease as PPCD1 (37 samples), PPCD3 (1 sample) and PPCDx (not linked to a known PPCD loci, 4 samples) or on the presence (17 samples) or absence (25 samples) of secondary glaucoma or on whether they had undergone penetrating keratoplasty (PK, 32 samples) or repeated PK (rePK, 7 samples). RESULTS: The level of active TGF-β2 in the AH of all PPCD patients (mean ± SD; 386.98 ± 114.88 pg/ml) in comparison to the control group (260.95 ± 112.43 pg/ml) was significantly higher (P = 0.0001). Compared to the control group, a significantly higher level of active TGF-β2 was found in the PPCD1 (P = 0.0005) and PPCDx (P = 0.0022) groups. Among patients the levels of active TGF-β2 were not significantly affected by gender, age, secondary glaucoma or by the progression of dystrophy when one or repeated PK were performed. CONCLUSION: The levels of active TGF-β2 in the AH of PPCD patients are significantly higher than control values, and thus the increased levels of TGF-β2 could be a consequence of the PPCD phenotype and can be considered as another feature characterizing this disease.
Keywords: transformující růstový faktor beta2; glaukom; Corneal Dystrophies, Hereditary; rohovka; Middle Aged; mužské pohlaví; Keratoplasty, Penetrating; rohovkový endotel; Aqueous Humor; Transforming Growth Factor beta2; Glaucoma; keratoplastika perforující; dědičné dystrofie rohovky; ženské pohlaví; Humans; komorová voda; Endothelium, Corneal; lidé středního věku; Female; Cornea; lidé; Male